The Socioscientific Issues Approach in Chemistry Education: A Literature Study and Its Implication - Prastika, Farera Nareswari Kirana; Arianingrum, Retno (FKIP Universitas Lampung, 2024)
Chemistry is often regarded as an unpopular subject among students, primarily because its learning process often disregards its relevance to students' everyday lives. Integrating socio-scientific issues (SSI) into chemistry education can bridge this gap by connecting chemistry concepts to students' real-life social experiences. Socio-scientific issues are socially relevant problems grounded in science that are inherently complex due to their intersection with multiple social factors, societal impacts, and the ethical dilemmas they often present. This study aims to explore the relationship between SSI-based chemistry learning, the relevance of chemistry education, students' social lives, and its benefits for students' learning. The research employs a Systematic Literature Review approach by analyzing 15 relevant articles retrieved from the ERIC and Scopus databases, selected based on established criteria and published within the last eight years. The findings from the reviewed literature indicate that incorporating SSI into chemistry education can enhance students' interest and motivation, improve their critical thinking and argumentation skills, and support their decision-making abilities. Keywords: socioscientific issues, chemistry learning, and relevance model.DOI: http://dx.doi.org/10.23960/jpmipa/v25i4.pp1880-1892